2015
DOI: 10.1088/0004-637x/815/1/7
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Alfvén Wave Generation by Large-Scale Phase Mixing

Abstract: One view of the solar-wind turbulence is that the observed highly anisotropic fluctuations at spatial scales near the proton inertial length d p may be considered as Kinetic Alfvén waves (KAWs). In the present paper, we show how phasemixing of large-scale parallel propagating Alfvén waves is an efficient mechanism for the production of KAWs at wavelengths close to d p and at large propagation angle with respect to the magnetic field. Magnetohydrodynamic (MHD), Hall-Magnetohydrodynamic (HMHD), and hybrid Vlasov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 70 publications
3
52
0
Order By: Relevance
“…This can be seen looking, for example, at δ B x and δ B z component (see Figures g and i], whose structure is progressively stretched in the shear regions. This process is slower than what is observed in the simulation by Vásconez et al [] since the in‐plane Alfvén velocity is smaller, due to the x component of B (0) that is now reduced by a factor cosπ/4. Another particular feature of this configuration is that the evolution is not symmetrical any more with respect to the line y = π .…”
Section: Numerical Resultsmentioning
confidence: 57%
“…This can be seen looking, for example, at δ B x and δ B z component (see Figures g and i], whose structure is progressively stretched in the shear regions. This process is slower than what is observed in the simulation by Vásconez et al [] since the in‐plane Alfvén velocity is smaller, due to the x component of B (0) that is now reduced by a factor cosπ/4. Another particular feature of this configuration is that the evolution is not symmetrical any more with respect to the line y = π .…”
Section: Numerical Resultsmentioning
confidence: 57%
“…However, we have neither examined the most general case, which would require full 3D simulations nor have we completely analyzed the compressible and kinetic effects in the present cases. In particular, not shown here are indications of specific kinetic wave modes and characteristic distortions of the velocity distribution function Vásconez et al 2015) that might be expected. A separate account of these results is in preparation.…”
Section: Discussionmentioning
confidence: 77%
“…Very thin current sheet structures and secondary ripples are observed only in the Vlasov case. The nature of these secondary ripples may be associated with the presence of some KAW-like fluctuations (Hollweg 1999;Vásconez et al 2015) and will be analyzed in detail in a separate paper.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Although KAWs have been observed in the magnetotail and ionosphere, their generation mechanisms and global transport properties are still unclear. Previous theories and simulations have shown that KAWs can be generated via various mechanisms such as magnetic reconnection (Liang et al, , ; Shay et al, ), mode conversion (Hasegawa & Chen, ; Johnson & Cheng, ), and phase mixing (Guo et al, ; Hasegawa, ; Vásconez et al, ). Shay et al () have shown the signature of KAWs generated by reconnection via a 2‐D particle‐in‐cell code.…”
Section: Introductionmentioning
confidence: 99%